Direct strength method for cold-formed steel beams with non-uniform temperatures. Issue 9 (20th September 2021) - Alabi-Bello, Mutiu; Wang, Yong; Su, Meini
Abstract : This paper presents the results of finite-element simulations leading to the development of a design method using the direct strength method (DSM) for transversely loaded thin-walled steel beams prone to local and distortional buckling failures at elevated temperatures. The systematic and extensive numerical parametric study covers different dimensions of thin-walled steel sections, different temperature distributions in the steel cross-section, different steel grades and different load ratios. The main findings are that DSM is a suitable method for thin-walled steel members with non-uniform elevated temperature distributions in the cross-section. Based on using the plastic moment capacity of the cross-section at elevated temperatures, the DSM equations in the existing specification by the American Iron and Steel Institute, as published in 2016, are sufficiently accurate for local buckling. For distortional buckling, a set of new DSM equations is proposed. The proposed DSM equations are then used to derive partial safety factors for structural resistance for conditional probabilities of structural failure of 0.1, 0.01 and 0.001 after flashover.